EFEKTIVITAS PROGRAM KOMUNITAS KEPROFESIAN BMKA SALMAN ITB - Salwa, Salwa; Nulhaqim, Soni Akhmad; Irfan, Maulana; Andayani, Rini Hartini Rinda (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2025)
This study aims to evaluate the effectiveness of the Professional Community program organized by BMKA Masjid Salman ITB in shaping alumni cadres’ professional readiness and character to face post-campus challenges. The scope of the research includes personal transformation, skills development, satisfaction with the mentoring system, and the sustainability of participants’ social contributions. A qualitative descriptive approach was employed, using semi-structured interviews with seven purposively selected informants actively involved in the program. The findings show that the program has had a positive impact on participants by transforming their perspective on profession as a form of service, enhancing technical and leadership skills, and fostering a mentoring ecosystem that encourages long-term relationships between generations of cadres. However, technical and accessibility challenges remain, especially regarding the hybrid format and limited openness to non-internal participants. Overall, the program is considered effective in shaping resilient and value-driven young professionals who contribute meaningfully to society, and it serves as a relevant model for value-based professional development in university settings.KEYWORDS: Professional Community, Youth Empowerment, Campus Mosque